The pedagogical status of ELT in China: challenges and issues - Chang, Zhong Lin (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2004)
There have been many kinds of teaching methodologies in ELT. Of these approaches, some were more popular than others in university teaching in China viz. the Grammar Translation method, the Audio-lingual method, the Communicative Approach. Among these approaches, the most dominant is the product-based, teacher-centred learning characteristic of the Grammar Translation method which has dominated ELT in China as seen in curriculum, textbooks and educational thinking. Though its place has been taken over by the Audio-lingual and the Communicative Method, its influence still remains.